2020
DOI: 10.1080/17452759.2019.1710919
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of lightweight and high-strength polymer-derived SiOC ceramics

Abstract: Lightweight and high-strength polymer-derived SiOC ceramics with varied lattice structures have been successfully produced using different polysiloxanes as preceramic polymers (PCPs) via photopolymerisation-based digital-light-processing 3D printing and pyrolysis. Photocurable precursor resins were prepared by simple mixing of polysiloxanes with photosensitive acrylate monomers, achieving good flowability and preserving desirable stability under different heating and oscillation conditions. Complex micron-size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(35 citation statements)
references
References 57 publications
(61 reference statements)
0
35
0
Order By: Relevance
“…It shows that ceramic parts with appreciable properties can only be obtained by pyrolyzing printed preceramic resins at temperature of ≥ 1000 ℃ (Fig. 8 (c)) [99]. www.springer.com/journal/40145 Similarly, Si 3 N 4 has also been reported using carbonfree polysilazane as precursor via DLP [100].…”
Section: Binary Polymer Derived Ceramicsmentioning
confidence: 96%
See 2 more Smart Citations
“…It shows that ceramic parts with appreciable properties can only be obtained by pyrolyzing printed preceramic resins at temperature of ≥ 1000 ℃ (Fig. 8 (c)) [99]. www.springer.com/journal/40145 Similarly, Si 3 N 4 has also been reported using carbonfree polysilazane as precursor via DLP [100].…”
Section: Binary Polymer Derived Ceramicsmentioning
confidence: 96%
“…Nonetheless, it is worth mentioning that pyrolysis temperature may influence the performance of final ceramic structures too [78]. It has in fact been discovered that the use of high pyrolytic temperature (≥ 1000 ℃) can lead to substantial phase transformation of the preceramic resins into SiC ceramic structures without clogging [70,78,99]. Specifically, Li et al [99] have revealed that there is possibility of having amorphous and crystalline phases at temperature of 600-800 ℃, and 1000 ℃ (Fig.…”
Section: Binary Polymer Derived Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is positive in showing the artistic expressive power of ink and painting, expressing the artist's artistic emotion, and showing the charm of oriental culture. Nowadays, traditional visual effects based on two-dimensional planes are gradually unable to meet people's needs for a higher quality of life [1]. More expressive three-dimensional displays are increasingly appearing in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the shapes of polymers could be tailored according to specific requirements after pyrolysis. At present, the most widely studied PDCs systems are mainly PDCs-SiC [5][6][7][8][9][10][11][12], PDCs-SiOC [13][14][15][16][17][18][19][20][21][22], and PDCs-SiCN [23][24][25][26][27][28][29][30][31][32] systems.…”
Section: Introductionmentioning
confidence: 99%